2005
DOI: 10.1186/bf03351830
|View full text |Cite
|
Sign up to set email alerts
|

Aftershock distribution and 3D seismic velocity structure in and around the focal area of the 2004 mid Niigata prefecture earthquake obtained by applying double-difference tomography to dense temporary seismic network data

Abstract: A destructive large earthquake (the 2004 mid Niigata prefecture earthquake) sequence occurred in the central part (Chuetsu district) of Niigata prefecture, central Japan on October 23, 2004. We have deployed a temporary seismic network composed of 54 stations for aftershock observation just above and around the focal area of the earthquake for about a month. Using travel time data from the temporary seismic network and surrounding routine stations, we obtained precise aftershock distribution and 3D seismic vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 17 publications
10
45
0
Order By: Relevance
“…This is the same as the previous compressional earthquakes as the 2003 northern Miyagi earthquake and others recently occurred in NE Japan (e.g. Okada et al, 2005Okada et al, , 2007a.…”
Section: Comparison Of the Aftershock Distribution With Thesupporting
confidence: 52%
See 2 more Smart Citations
“…This is the same as the previous compressional earthquakes as the 2003 northern Miyagi earthquake and others recently occurred in NE Japan (e.g. Okada et al, 2005Okada et al, , 2007a.…”
Section: Comparison Of the Aftershock Distribution With Thesupporting
confidence: 52%
“…This is the same as for the conjugate M 6 aftershock of the 2004 Mid Niigata (Chuetsu) earthquake (e.g. Okada et al, 2005). This might suggest eastward-dipping alignment may means relatively newly developed fault or the fault which is less developed in Miocene in comparison with the major westward-dipping fault plane.…”
Section: Comparison Of the Aftershock Distribution With Thementioning
confidence: 56%
See 1 more Smart Citation
“…Consequently, several research groups in Japan deployed temporary seismic stations following the mid-Niigata Prefecture Earthquake. Intensive researches such as hypocenter relocations, focal mechanism, seismic tomography and imaging of reflection planes or scatterings in the crust, have been conducted by several groups using data recorded at temporary seismic stations (e.g., Sakai et al, 2005;Kato et al, 2005a;Okada et al, 2005;Shibutani et al, 2005;Matsumoto et al, 2005). The results of the previous studies suggest that the complex structures associated with crustal stretching and folding have the potential to nucleate the mainshock and trigger a sequence of large aftershocks.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the slip is small for the high-velocity regions and large in the shallow low-velocity regions, and concluded that crustal structure heterogeneity could control the rupture process of the mainshock. A tomographic study of the 2004 mid-Niigata prefecture earthquake by Okada et al (2005) concluded that the high-velocity area with low V p /V s values, imaged in the footwall, was considered to be old basement rock, while, the low-velocity areas with high V p /V s values in the hanging wall were associated with sediments. Nakajima et al (2006) investigated the major features of the complex seismic velocity structure around the Nagamachi-Rifu fault in northeastern Japan, with implications for the existence of fluid-rich regions in the mid to lower crust as indicated by low velocity and high Poisson's ratio anomalies.…”
Section: Introductionmentioning
confidence: 99%